HUBUNGAN PENGETAHUAN TERHADAP PERSEPSI PEMBERIAN TERAPI PENCEGAHAN TUBERKULOSIS (TPT) PETUGAS PENGELOLA PROGRAM TB PUSKESMAS DI KABUPATEN SUMENEP - Trisno, Zetiawan; Hidayat, Adi Noval (Jurnal Riset Kefarmasian Indonesia, 2024)
Tuberculosis is a deadly infectious disease that ranks Indonesia second in the world. Providing Tuberculosis Preventive Therapy (TPT) is one of the strategies in TB control efforts. Knowledge of TPT by Puskesmas TB program officers plays an important role in encouraging the perception and behavior of TPT provision. TPT achievement in Sumenep District is still low (28%) in 2022. This study aims to determine how the relationship between knowledge and perceptions of TPT permissions of puskesmas program officers in Sumenep District. The research method used was analytical quantitative research with a cross sectional design. The population in this study were 30 TB program officers and the sample selection technique used total sampling. The results showed that most of the puskesmas TB program manager had good knowledge (63.33%) and the perception of providing TPT was positive (70%). The results of the statistical analysis test using chi-square showed p value (0.001) <0.05, OR = 23.8, then knowledge has a significant relationship on perceptions of TPT provision on puskesmas TB program manager in Sumenep district. Knowledge about TPT is positively related to perceptions on the dimensions of perceived susceptibility, perceived severity, health motivation and cues to action. The Sumenep district health office is expected to support the supervision of the implementation of the TPT administration program and provide training or refreshers to the Head of Puskesmas, doctors, Puskesmas TB program manager